Kinematic and dynamic analysis of new polar positioning system dedicated to mechatronic laser glass engraving system - Trochimczuk, Roman (Zielona Góra: Uniwersytet Zielonogórski)
Analytical formulas describing the kinematics and dynamics of a multibody system of a new polar positioning system dedicated to mechatronic laser glass or other transparent dielectrics engraving system will be presented in this work. The analytical results will become in the later stages of the research the basis of numerical simulations. They will optimize the proposed solution of the positioning system.
Keywords: polar positioning system; kinematic analysis; dynamic analysis; laser glass engraving